GSM TARMOQLARIDA MA’LUMOTLARNI UZATISHDA SIMCom MODULLARIDAN FOYDALANISH - Qudaybergenov, A.A.; Tadjiev, T.M.; Ametova, G.E. (SCIENCE and SOCIETY, 2021)
The article is primarily intended for those who are just starting to work with mobile modules from SIMCom Wireless Solutions, and can also be useful for experienced developers, since it reveals not always clear aspects of their work. The optimal sequence of IT commands is given, which eliminates the problems that arise when transmitting data received through sensor devices over the GSM network. In this way, the code of the managed program can be optimized mainly for the SIMCom Wireless Solutions modules, which enables faster activation and configuration of the modules. In general, this makes the program code more accurate and efficient.